Unravelling redox processes of Li7MnN4 upon electrochemical Li extraction–insertion using operando XAS. Issue 40 (3rd October 2017) - Muller-Bouvet, D.; Emery, N.; Tassali, N.; Panabière, E.; Bach, S.; Crosnier, O.; Brousse, T.; Cénac-Morthe, C.; Michalowicz, A.; Pereira-Ramos, J. P.
Abstract : Evolution upon electrochemical oxidation of the Li7 MnN4 Mn K-edge absorption spectra has been described using 3 distinctive local environments. Abstract : A large data set of XAS (X-ray Absorption Spectroscopy) Manganese K-edge spectra has been collected operando and studied upon the electrochemical oxidation of the promising Li-ion battery anode material Li7 MnN4 . Using chemometric tools such as PCA (Principal Component Analysis) and MCR-ALS (Multivariate Curve resolution – Alternating Least Squares), three independent environment spectra were insulated. Based on the faradaic yield and well-chosen comparison of absorption spectrum energies within the frame of the coordination charge model, these environments were ascribed to unusual oxidation states allowed by nitride chemistry at a low potential (∼1.2 V vs. Li + /Li), i.e. Mn 5+ (3d 2 ), Mn 6+ (3d 1 ) and Mn 7+ (3d 0 ). Also, their relative amounts are discussed with regard to the long-range structural variation which can be simply described by two successive biphasic domains followed by a solid-solution behaviour. Gathering this long-range and local structure information provides a complete picture of the redox mechanisms occurring in Li7 MnN4 .